2005
DOI: 10.1590/s1519-69842005000400003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dredging operations on soft bottom macrofauna in a harbor in the Patos Lagoon estuarine region of southern Brazil

Abstract: An evaluation was made of the effects of dredging on the soft bottom community in the channel of the Rio Grande harbor in the Patos Lagoon estuarine region of southern Brazil. During four seasonal cruises, samples were collected from nine biological stations, one of which was located outside the dredged area. Three macrobenthic samples were collected on each cruise from each station, using a 0.08 m2 van Veen grab. A cluster analysis was applied to group summer and autumn cruise stations before the dredging per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 12 publications
1
17
0
4
Order By: Relevance
“…Regarding the occurrence of species, recent literature was checked and data were compared with records provided for Patos Lagoon (Bemvenuti et al 2005), the states of Santa Catarina (Almeida et al 2012) and Paraná (Lana et al 2006), São Sebastião Channel (Pires-Vanin et al 2014), São Paulo continental shelf (Paiva 1993), Guanabara Bay (Santi and Tavares 2009) and Vitória Bay Estuarine System (Nalesso et al 2005). All taxa that occurred in this study were previously found in those regions.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Regarding the occurrence of species, recent literature was checked and data were compared with records provided for Patos Lagoon (Bemvenuti et al 2005), the states of Santa Catarina (Almeida et al 2012) and Paraná (Lana et al 2006), São Sebastião Channel (Pires-Vanin et al 2014), São Paulo continental shelf (Paiva 1993), Guanabara Bay (Santi and Tavares 2009) and Vitória Bay Estuarine System (Nalesso et al 2005). All taxa that occurred in this study were previously found in those regions.…”
Section: Discussionmentioning
confidence: 90%
“…Brazilian coast has 34 seaports and some studies have demonstrated degradation of sediment quality associated to port areas, with negative effects on benthic fauna (Bemvenuti et al 2005;Abessa et al 2008;Choueri et al 2009). Most investigations focused on ecotoxicological aspects of sediment contamination and their effects on soft-bottom communities, and thus, the record of the species has been poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…A atividade de dragagem em áreas costeiras constitui um impacto comum, seja para facilitar a entrada de navios em portos ou para execução de obras costeiras 22 . Dragagens promovem a remoção da camada superficial do sedimento, causando mudanças na estrutura e dinâmica das comunidades bentônicas, assim como dispersão na coluna d'água de poluentes eventualmente retidos no fundo 5,23 Apesar da destruição de habitats bentônicos e da elevada mortalidade de organismos durante o período de dragagem, ocorreu um incremento no número de espécies, de exemplares e biomassa, após o período de instabilidade; possivelmente influenciado pelo aumento da profundidade, melhoria dos padrões de circulação local e do maior ingresso de peixes no estuário.…”
Section: Siris E Camarõesunclassified
“…This variability is dependent on physical and chemical factors and biological interactions. Salinity fluctuations in estuarine systems have a strong influence on temporal patterns and daily and inter-annual variations; sediment characteristics have more influence on the spatial structure of benthic assemblages (Neves et al, 2012).Other factors should not be disregarded, since they can act in synergy (Bemvenuti et al, 2005). Benthic macrofauna in estuarine systems forms a mosaic of patches, which are maintained by a variety of disturbances and other biotic and abiotic factors (Morrisey et al, 1992).…”
Section: Introductionmentioning
confidence: 99%